Writing a business plan for a new venture - Douglas, Evan (Henry Stewart Talks, 2013)
Why write a business plan, The plan vs. the planning process, The five main sections of a business plan, The executive summary, The market opportunity, Market environment and competitor analysis, Competitive strategy, Marketing mix, Growth strategy, Production & supply chain management, Human resource management, Risk recognition and mitigation, Financial details and the investment opportunity, Business plan aesthetics, Brevity and parsimony, Page budget, Strategic omissions, Logical flow
Reviewed at 2016/03/31